Clinical application of adipose-derived stromal vascular fraction in 3 Thoroughbred horses with superficial digital flexor tendonitis: Case Report - TYRNENOPOULOU (Π. ΤΥΡΝΕΝΟΠΟΥΛΟΥ), P.; DIAKAKIS (Ν. ΔΙΑΚΑΚΗΣ), N.; ANGELOPOULOU (Σ. ΑΓΓΕΛΟΠΟΥΛΟΥ), S.; PYRROS (Α. ΠΥΡΡΟΣ), A.; MPAROUS (Ε. ΜΠΑΡΟΥΣ), E.; KOLIAKOS (Γ. ΚΟΛΙΑΚΟΣ), G.; KARAYANNOPOULOU (Μ. ΚΑΡΑΓΙΑΝΝΟΠΟΥΛΟΥ), Μ. (Journal of the Hellenic Veterinary Medical Society, 2018)
Tendon injuries are considered major causes of wastage in active Thoroughbred racehorses as they are among the most common musculoskeletal injuries in equine athletes. There has been considerable interest in the potential use of concentrated adipose tissue digest, such as stromal vascular fraction, in tendon overstrain injuries. It has been reported that the adipose-derived stem cells, which are present in stromal vascular fraction of adipose tissue, can promote neovascularization and improve healing process. The purpose of this study was to evaluate the potential effects of intralesional use of autologous adipose-derived stromal vascular fraction on tendon healing in three Thoroughbred active racehorses with moderate to severe superficial digital flexor tendonitis. Based on the results of this report it seems that intratendinous injection of autologous adipose-derived stromal vascular fraction leads to marked clinical improvement and reduction of rehabilitation period in racehorses suffering from superficial digital flexor tendonitis.